ANALISIS PERAN DANA DESA (DD) TERHADAP TINGKAT KEMISKINAN DI PROVINSI RIAU - Roni, Simanullang Roberto; Wahyu, Hamidi; Yusni, Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of village funds on poverty levels in districts / cities of Riau Province in 2015-2019 and to determine which districts are the most sensitive to village funds. This study uses secondary data in the form of panel data, namely 2015-2019 village funds and 2015-2019 poverty levels in Riau Province. Village fund data is obtained from DJPK.KEMENKEU, while poverty levels are obtained from the Central Statistics Agency of Riau Province 2015-2019. The analytical tools used in this research are SPSS and Elasticity. The results of this study indicate that partially the variable of the amount of village funds has a positive but insignificant effect on the poverty level in Riau Province in 2015-2019. This means that the greater the village funds provided, it actually increases the number of poor people in Riau Province, but the increase is not significant.Keywords: Village Fund and Poverty Level